Fertilization strategies that reduce emissions of nitrous oxide in forage grasses on farm in the low tropics - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Fertilizer sources and doses were identified to achieve higher forage productivity and N uptake, increasing these parameters up to 43%; for the conditions of the farm. The best-performing fertilizer-dose treatment allowed NUE of 93% and reductions of nitrous oxide emissions up to 40 % compared to other management practices.